Design of the Bali Province Food Security Action Plan towards Food Independence - WIDHIANTHINI, Widhianthini; SUKENDAR, Ni Made Classia; PURANTARA, Anak Agung Gede (Journal of Environmental Management and Tourism, 2024)
The problem of hunger is one of the problems that still occur in Indonesia. The problem of hunger is closely related to the problem of staple foods, such as the unmet security of staple food, rice as the community's main food, and the increasing demand for staple foods. This research aims to analyze the challenges faced by Bali Province in maintaining sustainable food security and to design food security action designs in Bali Province towards food independence. The data used in this research are primary data and secondary data with a descriptive analysis method using ISM analysis. The results of the research show that food challenges that occur in Bali Province include reduced agricultural land, unbalanced supply and demand for food commodities, weak use and mastery of technology, lack of farming management and product marketing, the proportion of crop loss and food waste is still quite high, food loss due to inaccuracy in handling food, the area of agricultural land per capita is very limited, the number of young people interested in working in the agricultural sector is still problematic, the age of farmers over 45 years reaches 64.2%, Indonesia is also still facing three times the burden of nutrition, climate change, and hydrometeorological disasters. The Bali Province's food security design towards food independence consists of farmers, government, companies, financial institutions, and agricultural cooperatives who are interconnected with each other.